Anterior Cruciate Ligament Reconstruction: Clinical Outcomes and Biomechanical Considerations of Graft Selection—A Narrative Review - Bogdan Huzum; Dan Viorel Cionca; Daniel Ciupilan; Cǎtǎlina Ionescu; Mihnea-Theodor Sîrbu; Malina Visternicu; Alin Ciobica; Oana Badulescu; Paul-Dan Sîrbu (Medicina, 2026)
Anterior cruciate ligament (ACL) reconstruction represents the current gold standard for restoring knee stability following ligament rupture, particularly in young and physically active individuals. The aim of this narrative review is to provide an updated overview of the biomechanical, biological, and clinical considerations underlying graft selection in ACL reconstruction, with particular emphasis on graft incorporation, fixation strategies, and postoperative outcomes. While surgical techniques and fixation devices have undergone substantial refinement, the optimal choice of graft remains a subject of ongoing debate. Traditionally, emphasis has been placed on the biomechanical characteristics of grafts, including tensile strength, stiffness, and resistance to cyclic loading. However, increasing attention has been directed toward biological factors that influence graft incorporation and clinical outcomes. The aim of this narrative review is to summarize the currently available literature regarding graft selection in ACL reconstruction by integrating biomechanical properties, biological graft incorporation, fixation strategies, and clinical outcomes. Particular emphasis is placed on the relationship between biomechanical performance and biological healing, as well as postoperative outcomes, in order to facilitate individualized graft selection in contemporary orthopedic practice.